2017
DOI: 10.2196/preprints.8990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

National Food, Nutrition, and Physical Activity Survey of the Portuguese General Population (2015-2016): Protocol for Design and Development (Preprint)

Abstract: BACKGROUND The assessment of food consumption data using harmonized methodologies at the European level is fundamental to support the development of public policies. Portugal is one of the countries with the most outdated information on individual food consumption. OBJECTIVE The objective of this study was to describe the design and methodology of the National Food, Nutrition and Physical Activ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
108
2
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(135 citation statements)
references
References 8 publications
8
108
2
17
Order By: Relevance
“…In the United States, total health-club members increased from 45.3 million in 2009 to 55.5 million in 2015 [ 4 ]. In Europe, namely in Portugal, 27% of those who engaged in exercise programs choose gym activities (vs. 15% in overall Europe) [ 5 ]. Furthermore, this seems to be a growing trend: the last report from the field points to an increase of 16% in Portuguese gym members between 2018 and 2019.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, total health-club members increased from 45.3 million in 2009 to 55.5 million in 2015 [ 4 ]. In Europe, namely in Portugal, 27% of those who engaged in exercise programs choose gym activities (vs. 15% in overall Europe) [ 5 ]. Furthermore, this seems to be a growing trend: the last report from the field points to an increase of 16% in Portuguese gym members between 2018 and 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Second, Portuguese society has been adopting unhealthy behaviors. Recent data revealed that Portuguese are mostly sedentary, their daily food intake is unbalanced (rich in sodium and sugar), they have the highest alcohol consumption rates in Europe and the percentage of smokers and illegal drug abusers is around 20% and 9.5%, respectively (DGS, 2016; Lopes et al, 2017; SICAD, 2016).…”
mentioning
confidence: 99%
“…The WHO COSI (Childhood Obesity Surveillance Initiative) study has shown a decrease in childhood overweight and obesity by almost 8% between 2008 and 2019, but more can be done. As of 2019, one-third of Portuguese children remained overweight or obese, a problem associated with inadequate eating habits: 69% of children do not consume the WHO-recommended 400 g of fruit and vegetables and 43% consume more than one soft drink on a daily basis [ 36 ].…”
Section: Resultsmentioning
confidence: 99%